Benefits of Plant Pigment, Quercetin, for Fish and Prawn - Prakoso, Yos Adi; Hidayah, Jasir Hakim; Sanjaya, Michael Richard; Pratama, Agga Dhigayuka; Azhar, Annisha Permata Nurul; Kuswanto, Arya Surya; April, Berlian Ronaldi; Utami, Intan Karisma; Putra, Mahera Sandi Sasmita; Wukak, Maria Paulina; Satria, Naufal Farros (UI Scholars Hub, 2024)
Quercetin is an important phytochemical that belongs to the flavonoid group of plant pigments. It has potential benefits as an antioxidant, antiviral, and anti-inflammatory agent. However, the utilization of quercetin in aquaculture is not optimal. Hence, this study conducted a literature review to analyze the potential benefits of quercetin in aquaculture, especially for fish and prawn. Results showed that quercetin can be isolated from herbs using several methods, including sonication, maceration, and fractionation. Its amount in plants can be potentially determined using high-performance liquid chromatography and thin-layer chromatography. Some of the plants containing high quercetin levels include shallot, garlic, apple skin, guava leaves, green tea, chia seeds, and desert rose flower. In aquaculture, quercetin can be applied to increase the ideal body weight, feed conversion ratio, and condition factor of aquatic cultured species and serves as an antioxidant, antistress, strengthening probiotic and an antiinfective agent. Latest research showed that quercetin benefits the immunity of goldfish against furunculosis. Furthermore, quercetin shows potential in prawn industry as an antioxidant protection that improves the meat quality. To date, the potential benefits of quercetin have not been widely utilized in aquaculture. The minimum utilization can be attributed to the lack of a systematic review regarding its potency either on fish or prawn. Hence, this study provides the essential review of quercetin in aquaculture.